Relational needs satisfaction scale: adaptation to the Bosnian language and psychometric testing - Mustoo-Başer, Lejla; Sinanović, Emina; Draganović, Selvira; Žvelc, Gregor (Frontiers in Psychology, 2025)
BackgroundRelating to others and establishing relationships is necessary for optimal human functioning. Perceived relational satisfaction appears to be one of the most important aspects of individuals’ lives, reflecting the extent to which our relational needs are met. This study aimed to test the factor structure, item characteristics, and convergent validity of the Bosnian adaptation of the Relational Needs Satisfaction Scale (RNSS).MethodA total of 420 participants (N = 420) completed the Relational Needs Satisfaction Scale (RNSS), the Relationships Questionnaire (RQ), and the Need for Drama Questionnaire (NFD). Descriptive statistics, reliability, and item analysis for the RNSS were conducted. Both exploratory and confirmatory factor analyses were conducted, along with a comparison of four models. The convergent validity of the RNSS was assessed by examining its association with two reference measures and their subscales: RQ and NFD.ResultsThe study showed that the translation was adequate, and the Bosnian version of the RNSS proved to be a reliable measure with mostly adequate item parameters. It confirmed that the RNSS structure can be interpreted as a five-factor model, comprising five dimensions and one higher-order factor, as well as a bi-factor model, where the variance of the items is simultaneously explained by a general factor and the five dimensions to varying degrees. The comparison of models and theory indicated the superiority of the bi-factor model.ConclusionThe adaptation of the RNSS Bosnian version demonstrated content validity, adequate measurement accuracy, and appropriate construct validity, as supported by confirmatory factor analysis. Furthermore, this study provides evidence that the translated RNSS is a valid and reliable instrument.